Prevalence of Mycoplasma bovis in bovine pneumonia and arthritis - Yeary, T.; Nietfeld, Jerome C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Samples from cattle with pneumonia and/or arthritis were cultured for Mycoplasma. When requested, the Mycoplasma isolates were further identified to species by polymerase chain reaction or restriction fragment length polymorphism. The records of all cases where mycoplasma testing was performed were examined and other infectious agents known to cause pneumonia or arthritis were recorded. Mycoplasma species were isolated from 85% of the lung samples and 69% of the joint samples. Eighty-four percent of the 81 Mycoplasma isolates that were further identified were M. bovis, which clearly made it the most common pathogenic agent identified in samples from cattle with pneumonia and/or arthritis. M. bovis appeared to play an important role in feedlot pneumonia and was the most common cause of arthritis. Unfortunately, treatment and prevention options are currently either ineffective or their effectiveness is unknown.
Keywords: Beef; Bovine; Pneumonia; Arthritis; Mycoplasma bovis